2020
DOI: 10.1007/s11356-020-08079-7
|View full text |Cite
|
Sign up to set email alerts
|

Influence of climate on energy consumption and CO2 emissions: the case of Spain

Abstract: This paper presents a methodology that allows for calculating the thermal and electric energy consumption together with CO2 emissions of cities by inhabitant and household based on climate, only making use of publicly available data. With this aim, climate was analysed and cities were classified based on it. The analysis of those cities' energy consumption and CO2 emissions allowed for drawing conclusions. Once aware of the climate zones in which energy consumption and emissions are higher, these mentioned con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 42 publications
2
23
0
Order By: Relevance
“…As some tech companies have started using solar and wind for power generation, other sectors will also follow this campaign to reduce their carbon footprint. This result validates the previous studies conducted for China (Akadiri et al, 2020;Munir & Riaz, 2020;Xu et al, 2015;Zhang, 2019); Spain (Zarco-Soto et al, 2020); South Asian economies (Munir & Riaz, 2019); Bangladesh (Shahbaz et al, 2014); ASEAN countries (Lean & Smyth, 2010); Pakistan (Rehman et al, 2019) and BRICS (Haseeb et al, 2019).…”
Section: Resultssupporting
confidence: 91%
“…As some tech companies have started using solar and wind for power generation, other sectors will also follow this campaign to reduce their carbon footprint. This result validates the previous studies conducted for China (Akadiri et al, 2020;Munir & Riaz, 2020;Xu et al, 2015;Zhang, 2019); Spain (Zarco-Soto et al, 2020); South Asian economies (Munir & Riaz, 2019); Bangladesh (Shahbaz et al, 2014); ASEAN countries (Lean & Smyth, 2010); Pakistan (Rehman et al, 2019) and BRICS (Haseeb et al, 2019).…”
Section: Resultssupporting
confidence: 91%
“…As some tech companies have started using solar and wind for power generation, other sectors will also follow this campaign to reduce their carbon footprint. This result validates the previous studies conducted for China (Akadiri et al 2020 ; Munir and Riaz 2020 ; Xu et al 2015 ; Zhang 2019 ); Spain (Zarco-Soto et al 2020 ); South Asian economies (Munir and Riaz 2019 ); Bangladesh (Shahbaz et al 2014 ); ASEAN countries (Lean and Smyth 2010 ); Pakistan (Rehman et al 2019 ); and BRICS (Haseeb et al 2019 ).…”
Section: Resultssupporting
confidence: 87%
“…Yorucu and Varoglu ( 2020 ) studied the nexus among industrial production, electricity consumption, economic growth, and CO 2 e in selected small island states. Based on the FMOLS and DOLS estimations, the authors found that a 1% increase in electricity consumption predicted an upsurge of 0.79% in CO 2 e. In the same way, other studies have also reported a positive connection between electricity consumption and CO 2 e for China (Akadiri et al 2020 ; Munir and Riaz 2020 ; Ou et al 2011 ; Xu et al 2015 ; Zhang 2019 ); Spain (Zarco-Soto et al 2020 ); South Asian economies (Munir and Riaz 2019 ); Bangladesh (Shahbaz et al 2014 ); ASEAN countries (Lean and Smyth 2010 ); Pakistan (Rehman et al 2019 ) BRICS (Cowan et al 2014 ; Haseeb et al 2019 ); and Kuwait (Salahuddin et al 2018 ). Table 4 depicts the summary of the selected studies on the nexus between electricity consumption and CO 2 e.…”
Section: Literature Reviewmentioning
confidence: 83%
“…where n i is the number of cities that belong to group i; E i is the mean energy consumed in group i; E ij is the energy consumption of city j, which is located in group i; s i is the standard deviation of the energy consumed in the cities of group i; the energy consumed will be thermal, electric or total depending on the case study; and cities consumptions should be listed in ascending order to calculate the median. An index analogous to that defined in [41] is used to analyze the energy consumption of cities. The density variation index (DVI) is defined as:…”
Section: Classification Of Cities By Population Densitymentioning
confidence: 99%
“…Although the influence of external factors has not been eliminated, it must be mentioned that the climate is one of those that may be of greater importance. That is why, to have a vision of the types of climates in which cities are located, Figure 2 shows the types of climates in Spain and the number of cities studied that are in each of them [41].…”
Section: Classification Of Spanish Citiesmentioning
confidence: 99%